Enhancing Elementary Students' Interest in Physical Geography: The Development of BENAPRO PBL-Based Interactive E-Module - Anggun Febriyanti; Arina Restian (Jurnal Pendidikan MIPA, 2026)
The challenge in teaching Natural and Social Sciences (IPAS) in elementary schools often lies in the difficulty of visualizing abstract concepts, particularly regarding landscape diversity and its relationship to community professions. Preliminary observations at Dadaprejo 01 Public Elementary School revealed a critical issue: fourth-grade students exhibited low engagement, characterized by a lack of focus and visible boredom during conventional lessons that relied heavily on static worksheets. Consequently, this study aims to develop the "BENAPRO" (Bentang Alam dan Profesi) e-module, designed to meet the criteria of validity, practicality, and effectiveness, specifically to increase students' interest in learning. This research employs a Research and Development (R&D) approach based on the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects in the field trial were 18 fourth-grade students. Data collection instruments included expert validation sheets, teacher and student response questionnaires using a Likert scale, and pre-test/post-test questionnaires to measure learning interest. The data were analyzed both descriptively and quantitatively. The results show that the e-module is "highly valid," with material experts providing an average score of 86% and product experts rating it at 96%. Practicality tests demonstrated excellent reception, with educators rating the module at 97.9% and students at 98.6%, citing the module's interactive features and ease of use. Crucially, the effectiveness test showed a significant surge in student interest, indicated by an N-Gain score of 0.82, which falls into the "High" category. It is concluded that the BENAPRO e-module is a valid, practical, and effective tool. By integrating Problem-Based Learning syntax with contextual visualization, this innovation effectively transforms passive learning into active engagement, making it a suitable alternative to the Independent Curriculum. Keywords: e-modules, natural and social sciences, diversity of landscapes and community professions, learning interests.